(3GdSMQ hGdTYQs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s ((3eMeO Hf CMeO Hf YjSi s)
(3ChdgG (B:s
(3hHYO aEfi deG bHV Gddg efi ddCOH eLdi SeGJgG , hfGTQ QeGMgG HYO eeGJgG Ydi HYO GdeOi, hehVY WQjbJgG GdeKdi s
(3BNQgG (B:s
(3bhd GdSHJi EPG MjhGf cGf Yeg VOg JhbGg cGdaGQ GPi jMPQ GdgQG hdGTc Gf GdeQA WYeg OgQg aeGHGdg jGhjMg jGef GdOgQG s
(3GdfSNI HgG MhGTs
(3JJab ChdgG eY GdfSNI Gdhdi cJHJ HNRGfI CejQ GdeDefjf GdefUhQ CMeO Hf CejQ GdeDefjf eMeO GdTjN GdTQjas
(3fSNI KGfjIs
(3Ydi ghGeTgG HYV GdJUjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
Keywords: (3GdCOHs